Missed opportunities for earlier diagnosis of HIV infection in people living with HIV in Thailand - Angsana Phuphuakrat; Kanitin Khamnurak; Sirawat Srichatrapimuk; Wittaya Wangsomboonsiri (Public Library of Science (PLoS), 2022)
HIV testing is the first step to making people living with HIV (PLHIV) aware of their status. Thailand is among the countries where antiretroviral therapy is initiated in PLHIV at the lowest CD4 cell counts. We aimed to quantify and characterize missed opportunity (MO) for earlier diagnosis of HIV infection in PLHIV in Thailand. The medical records of adults who were newly diagnosed with HIV between 2019 and 2020 at the two tertiary hospitals in Thailand were reviewed. A hospital visit due to an HIV clinical indicator disease but an HIV test was not performed was considered an MO for HIV testing. Of 422 newly diagnosed PLHIV, 60 persons (14.2%) presented with at least one MO, and 20 persons (33.3%) had more than one MO. In PLHIV with MO, the median (interquartile range) time between the first MO event and HIV diagnosis was 33.5 (7-166) days. The three most common clinical manifestations that were missed were skin manifestations (25.0%), unexplained weight loss (15.7%), and unexplained lymphadenopathy (14.3%). Anemia was a factor associated with MO for HIV diagnosis [odds ratio (OR) 2.24, 95% confidence interval (CI) 1.25-4.35; p = 0.018]. HIV screening reduced the risk of MO for HIV diagnosis (OR 0.53 95% CI 0.29-0.95; p = 0.032). In conclusion, MOs for earlier diagnosis of HIV infection occurred in both participating hospitals in Thailand. Skin manifestations were the most common clinical indicator diseases that were missed. HIV testing should be offered for patients with unexplained anemia. Campaigns for HIV screening tests should be promoted.